Pelatihan Pengelolaan Laporan Keuangan Sederhana Bagi UMKM Daerah Istimewa Yogyakarta - Mifah Khaerunnisyah; Nugraeni Nugraeni (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
This community service aims to determine the effectiveness of research on simple financial report management for UMKMs. This community service is carried out using quantitative methods with an experimental approach. The results of community service show that research on managing UMKM financial reports in food stalls is effective in increasing the knowledge and skills of UMKM actors in managing financial reports. This service has the implication that community service in managing financial reports can be an effort to improve UMKM financial management, so that it can increase the competitiveness of UMKM.